Factors associated with oral health related quality of life among pregnant women in Hospital Universiti Sains Malaysia - Saddki, Norkhafizah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2013)
This study was done to determine factors associated with oral health-related quality of life (OHRQoL) in pregnant;women .~;tt.Hospital Universiti Sa ins Malaysia. Systematic random san1pling was utilized to recruit 194 pregnant ·V.:ornen. S.el f-. . a9ministered questionnaires were used to obtain information on socio-demographic and obstetric profile, self repOrted oral health and oral health ·practices, and perceived barriers to oral health care services. OHRQoL was measured usin·g fhe ' S~(OtJIP)M .questionnaire. Additionally, clinical examination was performed. to determine caries experience using l;li.e . DMFT index and gingival and periodontal health using the Gingival Index (GI) and Commuruty Periodontal. lnaex (Clf . The prevalence of dental caries was 93.3% with a mean OMFT of 5.9 (SO 3.97). The prevalen~c of gingivitis: was 1o.o:w and the mean GI was 1.2 (SO 0.58). Almost half of the women (46.4%) presented with per.iodontal· pppkets,!:: ltm_m .. ' About one third (34%) of th'em experienced impact due .to oral health·problems: :rhe most common i mpacts_dpen.~~: were' discomfort due tq food ge~ting stuck in between teeth or dentures (20.6%) and feeling that oral health·prol:)lems !fl!l.d· .caused bad breath.(11.3%). The mean severity of impact was 10.1 (SO 7.1 D and the mean extent of impact .was p.?. ~SE> 1.25). Self-reported·bad breath (OR=4.40, 95%CI: 2.04,9.43), cavitated tooth (0R=5.28, 95%CI: 2.65,10 .. 51) and long waiting time to see dentist (OR= 2.23, 95%CI: 1.06,4.70) were found to be significantly associated with the prevalence of impact. Self reported bad breath and cavitated tooth also had signi ficant association (p<O.OOI) with extent and severity of ~mpa~t. The severity of ii:npact was also associated with age of the women (p=0.007). ·In conclusion, oral health stat4~~j preg_nn~t .women in :this 'study was pQoi: and their OHRQoL w~ also relatively poor,· Factors found to .~e ass<?:Chite,~· · ·. O~Qot.. ofthe worpel) were selfi-eported bad·breath, cav.itated tooth, :I.ong·waiti,n~time,to see .dentist,.andq-age;